Perbedaan Kejadian Dysmenorrhea Pada Penggunaan KB IUD dan KB Suntik 1 Bulan (Cyclofem) Di Klinik An-Nuur Baturan Colomadu Karanganyar - Akbar, Moh. Ilham; , dr. Anika Candrasari, M.Kes (2017)
Dysmenorrhea is defined as the occurrence of abdominal cramps due to uterine contractions during menstruation. One of factors influencing its occurrence is the use of contraception. The purpose of this study to analyze whether there is a difference between the occurrence of dysmenorrhea due to the use of IUD (Intra Uterine Device)and that due to the use of monthly injectable contraceptive (cyclofem) at Klinik (Clinic) Pratama An-Nuur in Baturan subdistrict of Colomadu district of Karanganyar regency. The present study belongs to Observational Analytical study using cross-sectional study design and Purposive Sampling Technique. The instrument includes dysmenorrhea questionnaires. A chi-square test was performed using SPSS 23.0 for Windows. This study result there is a difference between the occurrence of dysmenorrhea due to the use of IUD (Intra Uterine Device)and that due to the use of monthly injectable contraceptive (cyclofem). The number of women experiencing dysmenorrhea due to the use of the former contraceptive is 29 (82.9%), while the number of those experiencing dysmenorrhea due to the use of the latter is 15 (42.9%) with p-value of 0.001. Conclusion of this study there is a significant difference between the occurrence of dysmenorrhea due to the use of IUD (Intra Uterine Device)and that due to the use of monthly injectable contraceptive (cyclofem). Keywords : IUD (Intra Uterine Device), Cyclofem, Dysmenorrhea